High‐power‐factor light‐emitting diode lamp power supply without electrolytic capacitors for high‐pressure‐sodium lamp retrofit applications. Issue 8 (1st September 2013) - Alonso, J. Marcos; Calleja, Antonio J.; Gacio, David; Cardesín, Jesus; Lopez, Emilio; Dalla Costa, Marco Antonio; da Silva, Marcelo Freitas; do Prado, Ricardo Nederson
Abstract : A long‐life high‐power‐factor integrated converter able to supply light‐emitting diode (LED) lamps in high‐pressure‐sodium lamp retrofitting applications is presented. The proposed converter is the integration of a buck‐boost converter with a buck converter, thus providing the necessary high input power factor and voltage transformation ratio to supply the low‐voltage LED array from the mains. The analysis of the converter is carried out, and a design procedure is proposed. The design is also performed so that low capacitances are needed at the output of each semi‐stage. This allows for the use of long‐life film capacitors, thus matching the converter lifetime to that of the LED lamp. A laboratory prototype supplied from 230 Vrms /50 Hz mains used to drive two LED arrays in series with a total output power of 100 W is presented.